Dealing with China’s pension crisis - Gan, Y (2019)
Currently, the world faces many challenges. Among them, the largest and most serious problems include the “ageing issues”. Dealing with pension challenges is becoming an increasingly urgent agenda. In the case of China, this challenge is also prominent and significant, and has its own characteristics. The current mainstream Pillar I pension system is the Pay As You Go (PAYG) system, the funding of which relies heavily upon the real rate of economic growth. However, the economic weakness is one of the many challenges faced by many countries. In this context, many countries have established “Public Pension Reserve Funds (PPRFs)” to smooth benefit payments from PAYG system at the peak of population ageing. These PPRFs were designed to smooth short- to medium-term volatility in pension expenditures. They usually have long-term investment mandates while potential pension expenditure will occur far into the future. Against this background, China's National Social Security Fund (NSSF) is a typical PPRF. On the one hand, the NSSF shoulders the important mission of dealing with China's pension crisis. On the other hand, it is an important force in the Chinese capital market. It serves as both an important player and a platform bridging China's capital markets and pension challenges. Therefore, the success of the NSSF is, to a certain extent, the key to China's success in responding to the pension crisis. Thus, this research program sought to understand the genesis of the Chinese NSSF, focusing on the challenges facing China in terms of population ageing, the transformation of public and private systems of work and saving for the future, which underpins the early chapters of my thesis. In doing so, I have original and significant points to make about the development of the NSSF as well as the urgency of the issues to be faced now and in the future. In large part, this thesis takes models of best practice organization and management derived from research in the West and applies those to the NSSF. In doing so, it brings to light significant issues as to the organization and management of the institution while recognizing that it is an organization in transition. I try to get in and underneath the formal systems of the NSSF’s governance and management to bring to light actual practice. In doing so, the research has made a significant contribution to the literature informing social science in the West as well as the debate about institutional design in China. In terms of the research program, I have dug deep into Chinese sources at home and elsewhere to understand the logic and structure of Chinese policy-making, especially as regards the intersection between domain-specific expertise and broader interests, whether represented in the Party or in the highest reaches of the administrative apparatus. On one level, it is fairly simple to take existing intellectual and analytical frameworks and apply them to other areas of research. In this respect, this thesis could have been simply an analysis of the NSSF through the models of pension fund governance and management. These frameworks in action and their applicability to the Chinese situation has turned out to be a very important part of this thesis. In general, this thesis will make three significant contributions to the literature. First, I have provided notable insight as to the origins and development of the NSSF. This will obviously be highly regarded in the West, and will provide researchers around the world with significant information as to the development of one of the crucial welfare institutions of China. Second, I have delved deeply into the organization and management of the institution, through which we can see how the institution has developed in a short period of time regarding the ultimate mission of the institution. Whereas some pension institutions are criticized for their lack of innovation, this thesis has been able to document the changes made and the evolving nature of the institution in the Chinese case. Third, this thesis has the opportunity to say something fundamental about the application of global best practice to specific countries with very different traditions and from very different institutional formations. As such, this work will contribute to both in the Chinese case but also in Western social science.